2022
DOI: 10.3389/fendo.2022.854094
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Harmine on β-cell Function and Proliferation in Standardized Human Islets Using 3D High-Content Confocal Imaging and Automated Analysis

Abstract: Restoration of β-cell mass through the induction of proliferation represents an attractive therapeutic approach for the treatment of diabetes. However, intact and dispersed primary islets suffer from rapidly deteriorating viability and function ex vivo, posing a significant challenge for their experimental use in proliferation studies. Here, we describe a novel method for the assessment of compound effects on β-cell proliferation and count using reaggregated primary human islets, or islet microtissues (MTs), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 62 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…To address this, we utilized BDC2.5 transgenic NOD T cells, which express a pancreatic islet‐specific TCR that promotes cell trafficking to the pancreatic islets 69 . The NP‐Treg formulation was further optimized by dual loading of IL‐2 with harmine, which stimulates insulin‐producing β‐cell replication 70,71 . IL‐2/harmine NPs were coupled to BDC2.5 Tregs and administered to 12‐week‐old, pre‐diabetic female NOD mice, representing late stage intervention when significant insulin‐producing cell loss has already occurred 72 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this, we utilized BDC2.5 transgenic NOD T cells, which express a pancreatic islet‐specific TCR that promotes cell trafficking to the pancreatic islets 69 . The NP‐Treg formulation was further optimized by dual loading of IL‐2 with harmine, which stimulates insulin‐producing β‐cell replication 70,71 . IL‐2/harmine NPs were coupled to BDC2.5 Tregs and administered to 12‐week‐old, pre‐diabetic female NOD mice, representing late stage intervention when significant insulin‐producing cell loss has already occurred 72 .…”
Section: Resultsmentioning
confidence: 99%
“… 69 The NP‐Treg formulation was further optimized by dual loading of IL‐2 with harmine, which stimulates insulin‐producing β‐cell replication. 70 , 71 IL‐2/harmine NPs were coupled to BDC2.5 Tregs and administered to 12‐week‐old, pre‐diabetic female NOD mice, representing late stage intervention when significant insulin‐producing cell loss has already occurred. 72 While unconjugated IL‐2/harmine NPs did not prevent diabetes, animals that received IL‐2/harmine NP‐coupled BDC2.5 Tregs had significantly reduced T1D incidence versus the saline control group (Figure 8B ).…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, drug treatment studies at multiple time points (e.g., 3, 6, 9, 12 days) may be of interest, but human islets survive and retain phenotype poorly over more than a few days. In this regard, Title et al reported that reaggregated pseudoislets can be cultured and subjected to DYRK1A inhibitor treatment for up to 15 days 71 . These reaggregated pseudoislet models hold promise for longer term human islet studies.…”
Section: Discussionmentioning
confidence: 99%
“…It can add different cells or microorganisms to mediate cell-cell and cell-microbe interactions [ 100 102 ]. Microarray technology can also be combined with imaging instruments to monitor cell biological changes in real time, record behavioral changes of cells in disease states, and record the whole process of cellular response to drugs [ 103 105 ]. Microarray technology enables more systematic and mechanized organoid culture, increases throughput, expands the scope of research, and takes a firm step toward clinical translation [ 69 , 100 , 106 108 ].…”
Section: Intestinal Organoid Culture Technologymentioning
confidence: 99%